Data for "Shell microstructures (disturbance lines) of Arctica islandica (Bivalvia) – A potential proxy for severe oxygen depletion" - Höche, Nils; Zettler, Michael, L.; Huang, Xizhi; Schöne, Bernd, R. (Zenodo, 2022)
All data used in the publication "Shell microstructures (disturbance lines) of Arctica islandica – A potential proxy for severe oxygen depletion" currently under review. This includes in situ environmental data from the Mecklenburg Bight, Baltic Sea (ODIN 2, Leibnitz Institute for Baltic Sea Research, https://odin2.io-warnemuende.de/), and biomineral unit (BMU) morphology measurements in scanning electron microscopy images of shells of Arctica islandica , as well as the BMU classifier used in Ilastik (Berg et al., 2019). Each BMU measurement represents summary statistics of the 15 % largest BMUs within one image (25, 50 and 75 % percentile of each BMU parameter). Environmental data were measured at 20 m water depth, ca. 5 m above the sediment surface. Funding: BRS, SCHO793/22-1 and SCHO793/23-1, German Research Foundation, https://www.dfg.de/; The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the dataset.